Morphology Analysis of Hair Photoinduced and Chemical Damaged After Treatment with Sappan Wood (Caesalpinia sappan L.) Hair Tonic using SEM - Sari, Dina Yuspita; Widyasari, Ratna; Astuti, Indri (Borneo Journal of Pharmacy, 2023)
Exposure to sunlight for a long time and repeatedly can also cause chemical and physical damage to human hair. Clinically, microscopic analysis using a scanning electron microscope (SEM) can assess hair damage by identifying the characteristic morphology of hair damage. This study aims to analyze the morphology of damaged hair chemically induced using 3% H2O2 and photoinduced UVB radiation before and after applying sappan wood (Caesalpinia sappan) hair tonic. The active ingredients used were ethanol extract, ethanol fraction, and chloroform-methanol fraction of C. sappan, which contains an antioxidant compound. Caesalpinia sappan simplicia was macerated using 96% ethanol and then partitioned using n-hexane. The ethanol fraction was then applied using vacuum column chromatography using chloroform : methanol (5 : 1) as eluent. The extracts and fractions were then formulated into hair tonic preparations. For SEM analysis, hair samples were coated with a sputter gold coater machine and divided into five treatments: undamaged hair, damaged hair with 3% H2O2 and UVB rays as a positive control, and treatment I, II, and III, in which the hair was damaged with 3% H2O2 and UVB rays respectively, then FI, FII, and FIII were applied, respectively (2000x magnification). Damaged hair with UVB induction shows moderate damage, and 3% H2O2 shows moderate to severe damage. The results in the treatment group show that the three hair tonics coated the hair cuticle, indicating an interaction with the hair fiber, and modified the cuticle by coating the cuticle.